2020
DOI: 10.1007/s11886-020-01423-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of the Genetic Architecture of Dilated Cardiomyopathy

Abstract: Purpose of Review Dilated cardiomyopathy (DCM) frequently involves an underlying genetic etiology, but the clinical approach for genetic diagnosis and application of results in clinical practice can be complex. Recent Findings International sequence databases described the landscape of genetic variability across populations, which informed guidelines for the interpretation of DCM gene variants. New evidence indicates that loss-of-function mutations in filamin C (FLNC) contribute to DCM and portend high risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…Previous studies of human genetics have shown that there are multiple genes related to dilated cardiomyopathy (DCM) [ 26 29 ]. Based on RNA-Seq data obtained here from zebrafish heart, we summarized 30 DCM related genes homologous to human in zebrafish (Table 1 ), including cardiac actin, cardiac troponin, myosin heavy chain, myosin-binding protein, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of human genetics have shown that there are multiple genes related to dilated cardiomyopathy (DCM) [ 26 29 ]. Based on RNA-Seq data obtained here from zebrafish heart, we summarized 30 DCM related genes homologous to human in zebrafish (Table 1 ), including cardiac actin, cardiac troponin, myosin heavy chain, myosin-binding protein, and so on.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, individuals carrying RBM20 pathogenic variants are at a high risk of AR-DCM and early ICD implantation should be discussed [49]. We performed an exhaustive In 2012, Gu et al, reported an animal model with a deficient titin splicing identifying a loss-of-function mutation in RBM20 as the underlying cause for the pathological titin isoform expression.…”
Section: Rare Rbm20 Variants In Familial Dilated Cardiomyopathymentioning
confidence: 99%
“…Nowadays, individuals carrying RBM20 pathogenic variants are at a high risk of AR-DCM and early ICD implantation should be discussed [ 49 ]. We performed an exhaustive review of the literature concerning RBM20 and DCM published before October 2020.…”
Section: Rare Rbm20 Variants In Familial Dilatementioning
confidence: 99%
“…DCM is characterized by left cardiac enlargement owing to left ventricular dilation as well as reduced systolic function, which is not secondary to ischemia, valvular disease, and hypertension. It may result in heart failure with a noticeable rate of morbidity and mortality 1 3 . The impaired systolic function is observed in the initial stages; however, diastolic dysfunction in association with reduced ejection fraction will be present in the advance stages 4 .…”
Section: Introductionmentioning
confidence: 99%